Retinal Nerve Fiber Layer and Macular Ganglion Cell Layer Thickness in Subjects Suffering from Diabetes Mellitus: An Observational Study - Anujja Gharat; Nayana Anil Potdar; Salma Mohd Iqbal Tabani; Burhanuddin Kaidjoher Fakhri; Darshana B. Rathod; Twinkle Choksi (Delhi Journal of Ophthalmology)
Purpose: The purpose of this study was to investigate the relationship of retinal nerve fiber layer (RNFL) and ganglion cell–inner plexiform layer (GCIPL) thickness in between normal healthy eyes and those affected by diabetes mellitus (DM) and also associate it with the extent of the disease. Materials and Methods: This hospital-based observational case-control study was conducted at a major tertiary health care center to investigate the relationship of RNFL and GCIPL thickness using spectral-domain optical coherence tomography (SD-OCT). A total of 124 eyes were studied out of which 62 belonged to diabetic subjects and 62 were normal homogenous controls. Among the diabetics, 30 eyes had mild-to-moderate diabetic retinopathy (DR) and 32 eyes had no DR. Results: The peripapillary RNFL thickness was significantly thinner in the eyes of patients with DR compared to controls. Furthermore, it was significantly thinner when compared to the eyes of diabetic subjects with no DR. No significant statistical difference was observed when comparing RNFL thickness in diabetic subject’s eyes without DR and controls. Significant GCIPL thinning was noted in eyes with DR compared to control eyes. Furthermore, it was significantly thinner when compared to the eyes of diabetic subjects without DR. No statistical difference was observed when comparing GCIPL thickness in diabetic subjects’ eyes without DR and controls. No significant correlation was obtained of glycated hemoglobin with either RNFL or GCIPL thickness in the diabetic patients’ group. A multiple linear regression model showed DR status and duration of diabetes as the best explanatory variables for GCIPL loss in diabetic eyes. Conclusion: The results show that both processes, the visible diabetic microvascular changes and neurodegeneration as studied clinically by SD-OCT, are late complications of DM and are closely linked. Thus, a complex neurovascular interaction occurring simultaneously is an early event in the pathogenesis of DR.